Islamic Inheritance Law in The Modern Era: Contemporary Aspects and Applications - Hartomo Razy, Lorinza (Institut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2023)
This research aimed to understand and analyze Islamic inheritance law in the modern era in its contemporary aspects and application. Islamic inheritance law had unique characteristics as part of Islamic sharia, whose implementation couldnot be separated from aqidah (faith). A person did not receive or would receive inheritance according to the portion determined by Allah outside his would, and there was no need to ask for his rights. This research method used library research. Inheritance law, in its contemporary aspect, was a response to social and cultural changes and demands for gender equality in modern society. Over the past few decades, debates surrounding gender inequality in Islamic inheritance law and demands for inheritance law reform had intensified. Awareness of women's rights, technological developments, and changes in family and economic structures were the main factors driving reforms in inheritance law. This reform aimed to create justice and gender equality in the distribution of inheritance, as well as maintain the relevance of Islamic inheritance law in an ever-changing society.